The effect of microwave annealing on the electrical characteristics of lanthanum doped bismuth titanate films obtained by the polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Stojanovic, B. D.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2006)
Lanthanum doped bismuth titanate thin films (Bi3.25La0.75Ti3O12-BLT) were produced by the polymeric precursor method and crystallized in a domestic microwave oven and in conventional furnace. Using platinum coated silicon substrates configuration, ferroelectric properties of the films were determined with remanent polarization P-r and a coercive field E-c of 3.9 mu C/cm(2) and 70 kV/cm for the film annealed in the microwave oven and 20 mu C/cm(2) and 52 kV/cm for the film annealed in conventional furnace, respectively. The films annealed in conventional furnace exhibited excellent retention-free characteristics at low infant periods indicating that BLT thin films can be a promise material for use in nonvolatile memories. on the other hand, the pinning of domains wall causes a strong decay at low infant periods for the films annealed in the microwave furnace which makes undesireable the application for future FeRAMS memories. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: thin films; atomic force microscopy; dielectric properties; fatigue